2015
DOI: 10.1098/rsos.140343
|View full text |Cite
|
Sign up to set email alerts
|

The 20-item prosopagnosia index (PI20): a self-report instrument for identifying developmental prosopagnosia

Abstract: Self-report plays a key role in the identification of developmental prosopagnosia (DP), providing complementary evidence to computer-based tests of face recognition ability, aiding interpretation of scores. However, the lack of standardized self-report instruments has contributed to heterogeneous reporting standards for self-report evidence in DP research. The lack of standardization prevents comparison across samples and limits investigation of the relationship between objective tests of face processing and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
251
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(278 citation statements)
references
References 53 publications
(84 reference statements)
23
251
3
1
Order By: Relevance
“…The validity of the Kennerknecht et al (2008) questionnaire to tap insight into face recognition ability has been previously criticized (e.g., Shah et al, 2015), because it includes some items that are unrelated to the core face recognition impairment in CP. When we used a newly devised 77-item novel questionnaire that includes questions from everyday life situations where impairments in face recognition should appear, we found much larger correlations with the CFMT and face-matching test (~.30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The validity of the Kennerknecht et al (2008) questionnaire to tap insight into face recognition ability has been previously criticized (e.g., Shah et al, 2015), because it includes some items that are unrelated to the core face recognition impairment in CP. When we used a newly devised 77-item novel questionnaire that includes questions from everyday life situations where impairments in face recognition should appear, we found much larger correlations with the CFMT and face-matching test (~.30).…”
Section: Discussionmentioning
confidence: 99%
“…Bindemann et al, 2014). In contrast, the study using the recently developed PI20 questionnaire (Shah et al, 2015) suggests that people do have a great deal of 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 insight into their face recognition abilities: scores on the PI20 correlated highly (and as expected, negatively) with scores on a famous face task (r(171) = -.81, p < .001) and the CFMT (r(108) = -.68, p < .001). This level of insight is much higher than that reported for most other abilities.…”
Section: You Have the Impression Of Being Less Accurate Than Other Pementioning
confidence: 99%
See 1 more Smart Citation
“…One recent study developed a 20 item questionnaire and reported a strong correlation between scores on the objective Cambridge Face Memory Test (CFMT; Duchaine & Nakayama, 2006) and questionnaire scores (Shah, Gaule, Sowden, Bird, & Cook, 2015), yet the authors combined their typical participants and those with DP into one group for analysis. It is therefore unclear whether the effect sizes are driven by only one group, particularly because the participants with DP had already self-referred to the authors' laboratory for assessment.…”
Section: Developmental Prosopagnosia: Historical Backgroundmentioning
confidence: 99%
“…This is not to say that parental-or self-report measures cannot be useful in the identification of face recognition difficulties: Kennerknecht et al (2006) note that a subsample of the cases identified in their study also performed poorly on a variety of A c c e p t e d M a n u s c r i p t FACE RECOGNITION DEFICITS IN CHILDHOOD behavioural tests; and the recently developed PI20 (a self-report measure of face recognition difficulties; Shah, Gaule, Sowden Bird, & Cook, 2015) correlates well with performance on famous face identification tests and the adult version of the CFMT. However, neither of these tests is appropriate for children, and until a reliable parental report scale is developed, behavioural tests appear to be the most appropriate way of identifying face recognition deficits in children.…”
Section: Screening For and Identification Of Face Recognition Deficitmentioning
confidence: 99%